Pink illusions and white shifts - Stuart Anstis; Sae Kaneko; Patrick Cavanagh (i-Perception)
A rotating stimulus of alternating red and white sectors generates a faint pink fill throughout the image. The trailing cyan after images of the red sectors quickly become the brightest regions in the image, providing an index of the overall illumination that triggers a shift of the white point. Actual white areas then shift in the opposite direction and appear pink.